An Investigation of Soil Bearing Capacity for Building and Structural Foundation Design: A Case Study of Polo Area, Maiduguri, Nigeria. - Muhammad, I.S.; Alkali , A.M; Bulu, K. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2022)
The foundation of any structure is the back born of its stability against all kinds of deformation and this depends on the geotechnical behavior of the supporting soil. Clay soils usually posed serious threats to buildings due to shrink-swell behavior, settlements and low strength which is associated with their minerals. In this research, the safe bearing capacity of Polo soil have been investigated using direct shear laboratory analysis on twenty representative soil samples across virgin area where future development is approaching. Most of the soils were classified as lean clay with sand (CL) according to Unified Soil Classification System (USCS) although some were otherwise. The average natural moisture content of the soils at 1m depth is 8.38% with liquid limit and plasticity index of 30.2% and 15.7% respectively while that of 1.5m were 9.14%, 29.4% and 14.6% respectively. Results also revealed an average friction angle and cohesion of 21º and 18 kN/m2 at 1m and 22o and 19 kN/m2 at 1.5m depths respectively. Safe bearing capacity values ranges from 44.95 to 411.11 kN/m2 and 75.27 to 397.31 kN/m2 for 1m and 1.5m respectively using foundation widths of 0.5m, 1m and 2m. Foundation design carried out using the different safe bearing capacities and load combinations revealed that the pad footings analyzed with 1500 kN indicated that the minimum footing size that could be used is 1800mm×1800mm using 400kN/m2 safe bearing capacity. It also revealed that for a 100kN/m2 safe bearing capacity, the footing size is as much as 3500mm×3500mm which is very high and raft foundations were recommended for such situations.